PENGATURAN PRINSIP TRANSFER OF UNDERTAKING PROTECTION OF EMPLOYMENT (TUPE) DALAM DUNIA KETENAGAKERJAAN INDONESIA (DIANTARA POTENSI DAN HAMBATAN) - Agus Sudiarawan, Kadek (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015)DO - 10.24843/JMHU.2015.v04.i04.p18, 2015)
This research is aimed identifying the advantages of the regulation of TUPE principles, as well as inhibiting factors for outsourcing companies to apply the TUPE principles after the Decision of the  Constitutional Court Number 27/PUU-IX/ 2011. The research was conducted by using normative-empirical method. The data of the research consisted of primary data and secondary data. All of the collected data were analyzed using qualitative method. The results of this research were presented in a descriptive analysis report. The results of the research indicated he advantages that could be obtained by workers in relation with regulation of the TUPE principles included protection of wages, welfare and working requirements, protection of workers when the company was taken over, protection of workers when there is a change of outsourcing company and regulation of the right to file a lawsuit to the industrial relations court. The inhibiting  factors in the application of the TUPE principles in the  outsourcing companies after the  Decision of Constitutional Court  were the lack of socialization and supervision of the government, various legal loopholes of discrepancies between the implementing regulation and  the Decision of Constitutional Court, uncertainty severance regulation, assumptions that TUPE was a new burden which may disadvantage employers, and the lack of understanding of the workers related to their rights.
Keywords: TUPE, Legal Protection, Outsourcing, FTEC